Literature Review: Behavioral Accounting Research in Indonesia - Sandy, Sandy; Sulim, Dewi Siswanti; Munandar, Agus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research was conducted in several ways, namely categorizing the title, research technique, research participants, and total article citations. This research seeks to ascertain the trajectory of the development or progress of behavioral accounting research over 15 years (2007–2021). This research uses a qualitative descriptive methodology, and a literature review or literature study system is the basis for the data collection process. The articles examined come from journal sources that have been accredited or indexed by Sinta. The findings of this research confirm that (1) describing the title reveals that the title Planned Behavior Theory has six articles, Control Locus has four articles, Fraud has ten, Nature Machiavellian has three articles, and Love for Money has three articles. (2) the mapping is based on research techniques, so this approach uses a total of seven articles from experiments, fifty-two articles from surveys and questionnaires, four articles from interviews, six articles from case studies, and four articles from theory and non-empirical. source: (3) Based on the research subjects, the mapping shows that the subjects that use elements of academics/students are thirty-three articles, bankers are two articles, accountants or auditors are 14 articles, stakeholders or employees are nineteen articles, and taxpayers/ investors totaling three articles; (4) the total citations are only mapped to the top three points, so the TPB value is 33, LoC 55, Fraud 94, Machiavellian trait number 3, and LoM 31.